Mechanism Improvement and Process Optimization of the One‐Pot Synthesis of 3.7‐Dinitro‐1, 3, 5, 7‐Tetraazabicyclo[3, 3, 1]nonane from Urea. Issue 10 (2nd August 2018) - Zhu, Chao; Meng, Zihui; Liu, Yue; Xu, Zhibin; Song, Hongyan; Wang, Peng
Abstract: As a key precursor in the preparation of octahydro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocine (HMX), 3, 7‐dinitro‐1, 3, 5, 7‐tetraazabicyclo[3, 3, 1]nonane (DPT) prepared from urea by a modified one‐pot method has a bright future. On the basis of our previous work (Reaction Mechanism of One‐Pot Synthesis of Dinitro Pentamethylene Tetramine, Chinese Journal of Organic Chemistry 2010, 30 (3), 414–418.) [1], a novel intermediate 3‐nitro‐1, 3, 5, 7‐tetraazabicyclo[3, 3, 1]nonane was captured and isolated, and the key reactive intermediate hexahydro‐1‐nitro‐1, 3, 5‐triazine was directly captured and confirmed by HPLC‐MS. Thus, a modified synthetic mechanism for DPT was elaborated, and based which DPT preparation process was optimized. Abstract :